2018
DOI: 10.1177/0899764018756200
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Voluntary Nonprofit Accountability and Effects on Public Trust, Reputation, Perceived Quality, and Donation Behavior

Abstract: Voluntary accountability carried out by nonprofit organizations seeks to ensure organizational adherence to financial and ethical standards beyond legal regulations, thereby sending signals of quality and trustworthiness. Yet, insights into whether and how different forms of voluntary nonprofit accountability influence the public’s attitude are limited, and recent calls emphasize the need for further empirical investigation. Building on the combination of three different research streams, this article presents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
1
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(107 citation statements)
references
References 32 publications
5
84
1
10
Order By: Relevance
“…Therefore, accountability provides trust signals as information that is processed by donors in growing trust to the institution (or so-called institutional trust). This is proven with findings by Hasrina (2018) and Becker (2018) [24] [25]. An organization with high level accountability, (for example, having audited financial report) certainly has better signal of trustworthiness signal than the one which do not prepare any financial report.…”
Section: Trustsupporting
confidence: 55%
See 1 more Smart Citation
“…Therefore, accountability provides trust signals as information that is processed by donors in growing trust to the institution (or so-called institutional trust). This is proven with findings by Hasrina (2018) and Becker (2018) [24] [25]. An organization with high level accountability, (for example, having audited financial report) certainly has better signal of trustworthiness signal than the one which do not prepare any financial report.…”
Section: Trustsupporting
confidence: 55%
“…Willems et. al (2017) and Bies (2010) in Becker (2018) explain that the accountability of voluntary non-profit institutions (such as certification from outsiders) results in higher legitimacy and better reputation [25]. Khaerany (2013) found that the level of accountability has a positive influence on one aspect of reputation, which is quality [33].…”
Section: Reputationmentioning
confidence: 99%
“…This theoretical framework has been addressed in research in recent years to analyse different aspects related to CSR and social issues and its effects on several areas, including financial performance (Brower, Kashmiri, & Mahajan, ; Ferreira, ; Hamrouni, Miloudi, & Benkraiem, ; Jo & Harjoto, ; Muttakin et al, ); the risks of non‐compliance (Coleman, ; Datt, Luo, Tang, & Mallik, ; Groening & Kanuri, ; Luffarelli & Awaysheh, ; Reimsbach & Hahn, ; Wu & Hu, ; Xu, Zeng, Zou, & Shi, ); the signal of quality and future earnings (Basoglu & Hess, ; Moratis, ; Rupar, ; Siddique & Sciulli, ); obtaining competitive advantages and added value (Corazza, Scagnelli, & Mio, ; Yu, Kuo, & Kao, ). In recent years, the assurance of CSR has become relevant in this theoretical framework (Alon & Vidovic, ; Becker, ; Casey & Grenier, ). Finally, some research is centred on CSR in general or in terms of the environment, but philanthropy also occupies a special status among scholars (Haski‐Leventhal & Foot, ; Jia & Zhang, ; Liang & Renneboog, ; Shapira, ).…”
Section: Literature Review and Study Hypothesesmentioning
confidence: 99%
“…Authors also presented a second view on why trust is declining for charities-this view shall be termed "monitoring complexity." The view stipulates that monitoring complexity has increased due to a widely discussed theory referred as either the accountability problem (Becker, 2018) or as the principal-agent problem (Gugerty and Prakash, 2010). The problem can be explained as follows.…”
Section: Monitoring Complexitymentioning
confidence: 99%